Проблеми розробки та реалізації стратегії розвитку столичного мегаполісу - Галенко, О.М.; Крамаренко, Р.М. (Культура народов Причерноморья, 2013)
У статті розглянуто роль стратегії столичного мегаполісу як особливо важливого
інструменту його розвитку, проблеми її розробки та реалізації, зокрема необхідність врахування в ній
впливу сучасних тенденцій урбанізації. Розглянуто фактори впливу процесів глобалізації на розвиток
мегаполісів, а також різних аспектів її прояву. Обґрунтовується необхідність розвитку
методологічних та аналітичних досліджень у сфері управління мегаполісами в контексті впливу
глобалізаційних процесів, а також нових підходів щодо структурування проблематики міського
розвитку. В статье рассмотрена роль стратегии столичного мегаполиса как особенно важного
инструмента его развития, проблемы её разработки и реализации, в частности необходимость учета в
ней влияния современных тенденций урбанизации. Рассмотрены факторы влияния процессов
глобализации на развитие мегаполисов, а также различных аспектов ее проявления. Обосновывается
необходимость развития методологических и аналитических исследований в сфере управления
мегаполисами в контексте влияния глобализационных процессов, а также новых подходов к
структурированию проблематики городского развития. From the acceleration of globalization the world space has turned in extremely complicated, dynamic
and contradictory system of interactions and relationships. Mega cities in this system took place the centers of
flows almost all kinds of resources, fund, people and information. More apparent becomes substantial increase
of their economic power and political importance, rapidly increasing their role in the world economy and
international relations. The processes of urbanization in the world have reached a global level too, caused to the
transformation of a number of cities in the category of global cities - cities of global importance. They are not
only the autonomous structural elements of the global market, but also a sort of "remotes rule" of the global
economy and social relations.
In the article the role of strategy capital megapolis as particularly important instrument of development,
problems of development and implementation, including the need to integrate the impact it current trends of
urbanization. The factors the impact of globalization on the development of megacities, and various aspects of
its manifestation. The necessity of methodological and analytical research in the field of metropolitan areas in
the context of the impact of globalization and new approaches to structuring problems of urban development.